2020
DOI: 10.1007/s10584-020-02789-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rainfall structure and climate change on soil and groundwater salinization

Abstract: Irrigated areas, mainly in arid regions, are threatened by salinization processes. Climate change inducing temperature rise and rainfall depletion are expected to enhance these processes. Numerical models are often used to predict salinization in the root zone as well as water and solute fluxes reaching groundwater. Climatic data, mainly rainfall, have an important influence on the estimation of those fluxes. The present paper studies the impact of rainfall structure and climate change on soil and groundwater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Note that leaching processes were most active within important events of rainfall that took place in September (from 25 to 30th cumulative rainfall = 63 mm) and December 2016 (from 7 to 9th cumulative rainfall = 226 mm with 153 mm recorded on the 8th). Slama et al [53] found that rainfall structure had a noticeable impact on the solute leaching processes. Also, in arid and semi-arid Tunisia, the impact of rainfall on soil desalinization was more important for coarse than fine soil texture irrigated with brackish water [54].…”
Section: Impact On Solute and Water Return Flowsmentioning
confidence: 99%
“…Note that leaching processes were most active within important events of rainfall that took place in September (from 25 to 30th cumulative rainfall = 63 mm) and December 2016 (from 7 to 9th cumulative rainfall = 226 mm with 153 mm recorded on the 8th). Slama et al [53] found that rainfall structure had a noticeable impact on the solute leaching processes. Also, in arid and semi-arid Tunisia, the impact of rainfall on soil desalinization was more important for coarse than fine soil texture irrigated with brackish water [54].…”
Section: Impact On Solute and Water Return Flowsmentioning
confidence: 99%
“…As global climate change has intensified over the past several decades, arid and semiarid areas have been characterized by a negative moisture balance with evaporation exceeding precipitation ( Sered et al, 2011 ). Consequently, the decline in water volume has caused salinization to be the most concerning effect on lake ecosystems ( Slama et al, 2020 ; Ondrasek and Rengel, 2021 ). Concurrently, nutrient enrichment is also regarded as another most urgent environmental problem in arid and semiarid areas.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in low lying areas, other parameters such as the subsidence rate have also been employed [235]. A similar approach was used by Benini et al [236] in which climatic balances using predicted climate scenarios were established to derive a vulnerability index to salinization, or by Slama et al [237], who analyzed the pattern of precipitations and evapotranspiration via an unsaturated model to predict soil and groundwater salinization patterns. While Sušnik et al [238] used an interdisciplinary approach to assess sea-level rise and CC impacts on the lower Nile delta, Egypt, where CC effects should be studied in light of all the previously available data, as suggested by Mabrouk et al [226].…”
Section: Predictive Studies Of Coastal Aquifers' Salinizationmentioning
confidence: 99%